Quality Of Life of Elderly People in Institutional and Non- Institutional Setting: A Cross-Sectional Comparative Study - Praveen Kumar BA; Sharvanan Eshwar Udyar; Arun D; Shravan Sai (Medsci Publications, 2016)
Introduction: Ageing of the population along with changes in the family structure and shifts in intergenerational relations has brought into focus issues pertaining to health status across all domains, which in turn reflect the quality of life of elderly in India. This study was carried out with an objective to assess and compare the quality of life among elderly, residing in old age homes and in the community. Methodology: This study was carried out in the field practice area of PESIMSR, Kuppam, during June and November 2013. A total of 112 elderly were included in the study. Quality of life was assessed in four domains using WHO QOL (BREF) and the data was analyzed using SPSS software ver19. Results: Overall quality of life was low in both the groups. However, in the physical domain, institutional elderly had higher QOL (50.47 vs 47.18) and in the social domain, non institutional elderly had higher QOL (47.63 vs 33.60). Overall, 21.42% rated their QOL as good and 24.1% rated their health as satisfied. Socio-demographic variables were significantly related to QOL in social domain. Conclusion: Quality of life depends on multiple dimensions of well being which needs comprehensive assessment and multidimensional approach to improve.